Association of Anemia with Chronic Kidney Disease: A Tertiary Care Hospital Based Cross Sectional Study (KYAMC Journal, 2022)
Background: Chronic kidney disease (CKD) is a worldwide public health problem. It is usually associated with anemia and prevalence of anemia increases progressively with worsening CKD.Objective: To find out the association of anemia with different stages of CKD.Materials and Methods: This cross-sectional study was conducted in the department of physiology in Mymensingh medical college, Bangladesh over a period of one year from January to December 2016. A total number of 174 subjects were enrolled in this study among which 87 patients and 87 healthy participants. On the basis of inclusion and exclusion criteria study subjects were divided into case and control group. Hemoglobin concentrations in the blood were measured in all study subjects by using auto-analyzer.Result: Hemoglobin concentration in the blood was decreased in both male and female CKD patients which were 9.55±1.13 gm/dl and 9.11±0.95 gm/dl respectively and result was statistically significant (p